Leadership for Sustainable Economic Growth: Integrating AI, Policy, and Global Collaboration - Kabanda, Gabriel (JEBIM Prima, 2025)
Leadership in sustainability within the field of economics requires the ability to guide policies and strategies that prioritize environmental health, social equity, and long-term economic viability. This paper presents a framework for leadership that integrates the principles of the United Nations' Sustainable Development Goals (SDGs), emphasizing the role of Artificial Intelligence (AI) in identifying sustainability opportunities. Effective leaders must balance economic activities with their impacts on the environment and society, promote economic diversification, and advocate for sustainable practices through policy and regulation.The research employs an Integral Research methodology, combining descriptive, narrative, theoretical, experimental, and survey methods to explore leadership in sustainability. This approach considers the symbolic